Między przedmiotowością a życiem - Andrzej Gielarowski (Jesuit University Ignatianum in Krakow, 2017)
In the following article the author undertakes a key issue for contemporary philosophy of corporeality concerning the relation between objective body and subjective body. The most signiﬁ cant current discussions on the subject of human body centre around this differentiation, which appeared in phenomenology thanks to E. Husserl. "Body-Thing" (the Descartes' res extensa) was usually clearly distinguished, and even (in the Platonic-Cartesian current) separated from man's spiritual dimension (the soul, res cogitans). As a result, the vision of man dominating in the European culture for many centuries was marked by more or less distinct dualism. An effort to overcome the dualistic tension between the soul and the body was undertaken by two contemporary philosophers: Gabriel Marcel and Michel Henry. Both of them, in the developed different, though partly coincident, versions of the phenomenology of the human body, show the potential for such a presentation of human corporeality, in which the subjective dimension of human body is stressed, which allows to notice the unity of the incarnated human being. Yet the subject is not reduced to the material only, since the spiritual (I, ipse) "becomes part" of the essence of corporeality, which next to the visible aspect (the matter) has the invisible dimension, falling outside objectivization, which was traditionally called the soul.